2017
DOI: 10.1016/j.bbamem.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Differential binding of monovalent cations to KcsA: Deciphering the mechanisms of potassium channel selectivity

Abstract: This work explores whether the ion selectivity and permeation properties of a model potassium channel, KcsA, could be explained based on ion binding features. Non-permeant Na or Li bind with low affinity (millimolar K's) to a single set of sites contributed by the S1 and S4 sites seen at the selectivity filter in the KcsA crystal structure. Conversely, permeant K, Rb, Tl and even Cs bind to two different sets of sites as their concentration increases, consistent with crystallographic evidence on the ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 63 publications
6
26
0
Order By: Relevance
“…The second set of sites i) results from the contribution of all S1 through S4 crystallographic sites, ii) is available only to permeant cations when the filter is in the conductive conformation and iii) shows low affinity (millimolar K D 's), thus, favoring cation dissociation and permeation. The differences in affinities between permeant and non-permeant cations and the similarities in binding behavior within each group correlate fully with their permeabilities relative to K + and therefore, it was concluded that cation binding may be an important determinant of ion selectivity (31). Here we report new evidences that greatly reinforce such hypothesis.…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…The second set of sites i) results from the contribution of all S1 through S4 crystallographic sites, ii) is available only to permeant cations when the filter is in the conductive conformation and iii) shows low affinity (millimolar K D 's), thus, favoring cation dissociation and permeation. The differences in affinities between permeant and non-permeant cations and the similarities in binding behavior within each group correlate fully with their permeabilities relative to K + and therefore, it was concluded that cation binding may be an important determinant of ion selectivity (31). Here we report new evidences that greatly reinforce such hypothesis.…”
Section: Introductionsupporting
confidence: 73%
“…Figure 2 illustrates the first of such approaches in which the channel in a nonconductive state caused by 100 mM Na + , was titrated with the permeant K + , Rb + or Cs + . Similarly to that observed under non-competitive conditions (35), i.e., where titrations started with a channel prepared in just 1.5 mM Na + , the addition of increasing concentrations of any of the permeant cations, resulted in a large thermal stabilization of the channel protein ( Figure 2A, B and C). This indicates that all such permeant cations can efficiently displace Na + from binding to the channel pore; although K + and Rb + were always more efficient in this regard than Cs + .…”
Section: Cation Binding To Kcsa Under Competitive Conditionsmentioning
confidence: 89%
See 3 more Smart Citations